The influence of the anion exchange membrane on mass-transport limiting phenomena in bipolar interface fuel cells with Fe–N/C based cathode catalyst layers. Issue 50 (23rd September 2021) - Seeberger, Dominik; Hauenstein, Pascal; Hartert, Adrian; Thiele, Simon
Abstract : The AEM layer content in a bipolar interface fuel cell enables the opportunity to regulate the influx rate of water into the porous layer. Abstract : Water management is a very important issue in low temperature fuel cells such as proton exchange membrane fuel cells (PEMFCs) or anion exchange membrane fuel cells. Within bipolar interface fuel cells, water management inhibits an even more critical role. The earlier work on bipolar interface fuel cells (BPIFCs), employing Fe–N/C on the cathode side for the oxygen reduction reaction (ORR) in an alkaline environment, demonstrated increased stability of the catalyst compared to the acidic environment of the conventional PEMFCs. However, for the BPIFCs, severe mass transport limitations (MTL) dramatically reduced the power output of the cell within a few hours. In the present work water transport processes are identified as the source of the observed MTL, after evaluating the performance data of BPIFCs, where the amount of directly deposited anion exchange membrane (AEM) material was varied. It can be seen that the BPIFCs with lower AEM content show an earlier onset of MTL than the cells prepared with higher AEM content. It is shown that the AEM can be used as a tool to regulate the influx rate of product water from the bipolar interface into the CCL and that flooding of the porous layers is identified as the main source of the observed MTL. This work paves the way for further development of BPIFCs using Fe–N/C at the cathode electrode, as novel cell design strategies can now focus exclusively on avoiding flooding phenomena.